Modes of drug elimination and bioactive metabolites. Issue 9 (September 2017) - Chillistone, Shruti; Hardman, Jonathan G.
Abstract: Drug elimination is the removal of active drug from the body. Metabolism takes place largely in the liver and produces water-soluble metabolites which can be excreted in the bile or urine. Metabolism may also produce active or toxic metabolites or a pharmacologically active drug from an inactive prodrug. Most volatile anaesthetics are excreted unchanged via the lungs. Drug elimination can be affected by factors such as first-pass metabolism, genetic variants and various disease processes. Knowledge of these processes will allow better prediction of pharmacokinetics in practice.